Global burden, distribution, and interventions for infectious diseases of poverty - Bhutta, Zulfiqar A (BioMed Central, 2014)
Infectious diseases of poverty (IDoP) disproportionately affect the poorest population in the world and contribute to a cycle of poverty as a result of decreased productivity ensuing from long-term illness, disability, and social stigma. In 2010, the global deaths from HIV/AIDS have increased to 1.5 million and malaria mortality rose to 1.17 million. Mortality from neglected tropical diseases rose to 152,000, while tuberculosis killed 1.2 million people that same year. Substantial regional variations exist in the distribution of these diseases as they are primarily concentrated in rural areas of Sub-Saharan Africa, Asia, and Latin America, with geographic overlap and high levels of co-infection. Evidence-based interventions exist to prevent and control these diseases, however, the coverage still remains low with an emerging challenge of antimicrobial resistance. Therefore, community-based delivery platforms are increasingly being advocated to ensure sustainability and combat co-infections. Because of the high morbidity and mortality burden of these diseases, especially in resource-poor settings, it is imperative to conduct a systematic review to identify strategies to prevent and control these diseases. Therefore, we attempted to evaluate the effectiveness of one of these strategies, that is community-based delivery for the prevention and treatment of IDoP. In this paper, we describe the burden, epidemiology, and potential interventions for IDoP. In subsequent papers of this series, we describe the analytical framework and the methodology used to guide the systematic reviews, and report the findings and interpretations of our analyses of the impact of community-based strategies on individual IDoPs.